A structured survey on the usage of the issue tracking system provided by the GitHub platform - Marco Neto, Casimiro Conde; Barros, Márcio de O. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2017)
Issue tracking systems help software development teams in identifying problems to be solved and new features to be added to a software system. In this paper, we replicate and extend a study carried out in 2013 on the usage of the issue tracking system provided by the GitHub platform. The replication aims at determining whether the results observed four years ago are still valid. The extension seeks to analyze how often issues are terminated by commits to the version control system and understand whether this feature allows developers to relate an issue to the source code modules that were changed to resolve it. We conclude that the results of the previous study remain valid and that issues closed by commits are uncommon (about 4% of our sample) and often linked to technical aspects of the project.